2004
DOI: 10.1068/p5256a
|View full text |Cite
|
Sign up to set email alerts
|

Judging Egocentric Distance on the Ground: Occlusion and Surface Integration

Abstract: On the basis of the finding that a common and homogeneous ground surface is vital for accurate egocentric distance judgments (Sinai et al, 1998 Nature 395 497–500), we propose a sequential-surface-integration-process (SSIP) hypothesis to elucidate how the visual system constructs a representation of the ground-surface in the intermediate distance range. According to the SSIP hypothesis, a near ground-surface representation is formed from near depth cues, and is utilized as an anchor to integrate the more dista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

17
147
1
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(167 citation statements)
references
References 37 publications
17
147
1
2
Order By: Relevance
“…This integration process hypothesis was supported by Z. J. He et al (2004). They found that when there was an occluding box between a participant and a target object on the ground, the distance of the target object was underestimated.…”
supporting
confidence: 61%
See 2 more Smart Citations
“…This integration process hypothesis was supported by Z. J. He et al (2004). They found that when there was an occluding box between a participant and a target object on the ground, the distance of the target object was underestimated.…”
supporting
confidence: 61%
“…In recent years, a number of investigators have proposed similar ideas (Z. J. He, Wu, Ooi, Yarbrough, & Wu, 2004;McCarley & Z. J. He, 2000;Nakayama, Z. J.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our manipulation of an organizational factor was motivated by recent work in perception that has implicated surfaces-and ground surfaces, in particular-as structures for integrating object and scene information (e.g., He, Wu, Ooi, Yarbrough, & Wu, 2004;Ni, Braunstein, & Andersen, 2005;Vecera & Palmer, 2006; see also Gibson, 1979). Stimulus elements were selected from an organized pair of surfaces (ground and sky, Figure 1A) or an unorganized pair of surfaces (random arrangement of the same elements, Figure 1B).…”
Section: Methodsmentioning
confidence: 99%
“…Researchers attribute this overestimation to optical factors such as reduced brightness contrast or seemingly increased aerial perspective. However, above ground, reduced cue settings can result in distance compression (eg He et al 2004), so distance underestimation may have been expected underwater where optical cues are reduced. In the current experiment, participants viewed the same environment, so all optical cues were held constant across conditions.…”
mentioning
confidence: 99%